Metabolic syndrome and the risk of breast cancer among postmenopausal women in north-west China. (2nd November 2015) - Wang, M.; Cheng, N.; Zheng, S.; Wang, D.; Hu, X.; Ren, X.; Pei, H.; Ma, H.; Mu, H.; Bai, Y.
ABSTRACT: Objective  To determine whether metabolic syndrome (MetS) and its components are risk factors for breast cancer among postmenopausal women in China. Methods  Based on the baseline data of the Jinchang Cohort, a case–control study was carried out among postmenopausal women, including 43 cases and 86 controls. Both MetS and its components were evaluated. Odds ratios and 95% confidence intervals (CI) for the association were estimated by conditional logistic regression analysis. Results  The odds ratio of postmenopausal breast cancer was 3.505 (95% CI 1.282–9.583) for MetS, 3.016 (95% CI 1.044–8.715) for body mass index (BMI) ≥ 25 kg/m 2, and 3.191 (95% CI 1.253–8.125) for dyslipidemia. There was no significant association between postmenopausal breast cancer and hypertension as well as diabetes. Women with four metabolic factors showed greater risk for postmenopausal breast cancer ( p trend  < 0.05). Dyslipidemia and BMI ≥ 25 kg/m 2 showed most significant interaction on breast cancer (odds ratio = 11.359; 95% CI 2.663–48.450). With BMI ≥ 25 kg/m 2, the interaction of dyslipidemia and other metabolic factors on breast cancer was higher than that without BMI ≥ 25 kg/m 2 . Conclusion  This case–control study suggested that MetS was associated with an elevated risk of breast cancer among postmenopausal women in north-west China. Overweight and dyslipidemia had the strongest adverse effects on postmenopausal breast cancer.